Characteristics Of Family Support With Anxiety Levels For Palliative Cervical Cancer Patients At dr.Chasan Boesoerie Ternate City - Nursia Aja; Didik Kurniawati (International Journal of Health and Pharmaceutical (IJHP), 2022)
Cancer is a disease caused by abnormal growth of cells body tissue that is in the body changes into cancer cells. The purpose of this study was to study the characteristics of family support and anxiety levels of palliative cervical cancer patients at dr. Chasan Boesoerie, Ternate City. This type of research is an analytical observational study with a cross-sectional cross-sectional technique, to describe and assess several characteristics of family support with anxiety levels of palliative cervical cancer patients. The population in this study were all mothers who examined cervical cancer at dr. Chasan Boesoirie 2021, 47 mothers. The sampling technique was carried out with the total sample. That is equal to 47 mothers with cervical cancer. Results: The results of the study show that the age of mothers who are not at risk is 66.0%, while the frequency of respondents with civil servant jobs is 40.4%, compared to the work of IRT/Not Working mothers of 10.6%, compared to good knowledge of 61, 7% compared to the knowledge of the mother less by 38.3%, and good family support by 55.3% compared to the less family support by 44.7%, while the greater source of information is in the newspapers by 66.0% compared to social media, namely by 34.0%. Conclusion: There needs to be cooperation from health workers, for example from hospitals, always providing information about cervical cancer, always checking regularly with obstetricians to avoid things that can trigger disease growth and can prevent cancer triggers.